On (i,j) -prw Closed Set and (i,j)-prwContinuousfunction in BitopologicalSpaces - Luma Saad Abdual Baqi (Al-Qadisiyah Journal of Pure Science, 2017)
In this paper we introduce and study the a new class of closed set called (i,j)-preregular weakly closed set (briefly (i,j)-prw closed).and  (i,j)- pre weakly closed set (briefly (i,j)-pw closed).Moreover the notions of (i,j)-prw- Continuous function and (i,j)- pw- Continuous function are introduced ,and study the relationships  among them, are studied.